Living in the grip of relentless grace the gosspel in the lives of Isaac and Jacob - Duguid, Iain M. (Phillipsburg, NJ Presbyterian and Reformed, 2002)
Includes bibliographical references and index.
Keywords: Isaac (Biblical patriarch).; Jacob (Biblical patriarch).; Bible. O.T. Genesis -- relation to the New Testament; Bible. N.T. -- relation to the Old Testament; Bible. O.T. Genesis XXV-XXXVI -- criticism, interpretation, etc